Geopolymers in construction = Zastosowanie geopolimerów w budownictwie - Błaszczyński, Tomasz; Król, Maciej R. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Within the framework of quests of supplementary and ?healthier? binders to the production of concrete followed the development of geopolymers in construction. However the practical application of these materials is still very limited. The production of each ton of cement introduces one ton of CO2into the atmosphere. According to various estimations, the synthesis of geopolymers absorbs 2-3 times less energy than the Portland cement and causes a generation of 4-8 times less of CO2a very high fire resistance and also a high resistance to UV radiation.
Keywords: trwałość; geopolimery; betony geopolimerowe; emisja CO2; geopolymers; geopolymeric concretes; durability; CO2 emission